"Dhakirat al-alam": Palestinian traumatic memory in three works by Elias Khoury - Tewfik, Nourhan (AUC Knowledge Fountain, 2019)
This thesis project traces the development of a Palestinian counter-narrative of trauma in the literary works of Lebanese novelist, editor and critic Elias Khoury. It does so by looking at three novels by Khoury: the first work is Mamlakat al-ghurabā’ (The Kingdom of Strangers, 1993), which introduces his project on narrating the Palestinian experience and meditates on the potential structure of a Palestinian trauma narrative. Probably his most read work, the second novel, Bāb al-shams (Gate of the Sun, 1998), builds on these beginnings by re-enacting an incomplete, fragmented and non-teleological narrative of Palestinian traumatic memory. The same preoccupation with the history of Palestinian trauma figures in Khoury’s āwlād al-ghitu, ismī Adam (Children of the Ghetto, My Name Is Adam, 2016) which raises the question of identity in relation to trauma and digs deep into how traumatic events interrupt and reshape one’s self. Equally important is how all three works bring together Palestinian and Jewish traumatic histories analogously to disrupt Israeli hegemonic meta-narratives and propose both traumatic experiences as mirrors for other histories of suffering.